ANALISIS PRAKTEK LARANGAN MAYSIR, GHARAR, DAN RIBA DALAM ASURANSI SYARIAH DI INDONESIA - Desita Fitriani; Fauzatul Laily Nisa (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This abstract presents an analysis of the practices of prohibiting maysir, gharar, and riba in Sharia insurance in Indonesia. The research highlights efforts to implement Sharia principles in the insurance industry, focusing on avoiding practices that contradict Islamic values. Through a qualitative and descriptive approach, this study examines the steps taken to prevent maysir, gharar, and riba in Sharia insurance operations. Findings indicate structured efforts, such as the use of appropriate Sharia contracts and oversight by the Sharia Supervisory Board. The concept of Sharia insurance, emphasizing solidarity and justice, serves as the foundation for upholding Sharia principles in this industry. However, there are still challenges to overcome, such as a shortage of experts and the need for improved claims services for the public. Thus, this research provides insights into the development of Sharia insurance in Indonesia and the necessary steps to ensure compliance with Sharia principles in this industry.